2016
DOI: 10.1111/ane.12583
|View full text |Cite
|
Sign up to set email alerts
|

No associations between five polymorphisms inCOMTgene and migraine

Abstract: Our results indicate that the five polymorphisms in COMT have no association with migraineurs in Western Japan. The possibility that segments elsewhere in the gene may contain a mutation responsible for modifying the expression of COMT or the activity of the enzyme is important. We cannot conclusively exclude the entire COMT gene from being involved in migraine pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 23 publications
2
17
0
1
Order By: Relevance
“…Numerous studies in the past few decades have clearly shown that synonymous single-nucleotide polymorphisms (SNPs) do not produce altered coding sequences, and therefore they are not expected to change the expression and function of the protein in which they occur (32)(33)(34)(35). However, according to recent research, the synonymous SNPs can affect protein expression by alteration or increase in the stability of the mRNA (38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in the past few decades have clearly shown that synonymous single-nucleotide polymorphisms (SNPs) do not produce altered coding sequences, and therefore they are not expected to change the expression and function of the protein in which they occur (32)(33)(34)(35). However, according to recent research, the synonymous SNPs can affect protein expression by alteration or increase in the stability of the mRNA (38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 Haplotype production approach for UGT2B7, ABCB1, OPRM1, and COMT. [48][49][50][51][52][53][54][55][56][57][58] Due to lack of empirical data for each polymorphism, additional damaging or most likely damaging polymorphisms in a gene were assumed to completely eliminate enzyme function. Logistic regression was used to explore possible relationships between the well-characterized CYP2D6-inferred metabolizer phenotype, represented as an activity score (a qualitative measure of phenotype derived from the activity conferred by each * allele an individual carries [54]) and the predicted activity of UGT2B7, ABCB1, OPRM1, and COMT.…”
Section: Methodsmentioning
confidence: 99%
“…Forensic Science International: Genetics 33 (2018) [48][49][50][51][52][53][54][55][56][57][58] differentiate the relationships between haplotypes; alternatively, the substantial reticulation in the OPRM1 and COMT haplotype networks might also suggest some degree of recombination between the regions of interest. Most major haplotypes in all four genes were observed in all five super-populations while many minor haplotypes were unique to one super-population, namely African (i.e., UGT2B7 haplotypes stemming from UGT2B7-H19).…”
Section: Fr Wendt Et Almentioning
confidence: 99%
See 2 more Smart Citations